AN ANALYSIS OF COHESION ON WRITING COMPARATIVE PARAGRAPH OF ENGLISH DEPARTMENT STUDENTS UNIVERSITAS RIAU KEPULAUAN IN THE ACADEMIC YEARS OF 2015/2016 - Desi Surlitasari Dewi (Universitas Riau Kepulauan, 2015)
The objective of the research was to answer the research question which was to analyze grammatical cohesion and lexical cohesion of comparative paragraph produced by third semester students of English Department Universitas Riau Kepulauan. The research was conducted in three months starting from observing the sample to making report. This research was held on third semester students of English Department Universitas Riau Kepulauan in academic year 2015/2016. The research method used was qualitative study. The subject of the research was third semester of English Department Universitas Riau Kepulauan. There were several techniques to collect the data that was used in conducting a research, namely observation, questionnaire, interview, and test. In this research, the researcher conducted a writing test to get the data. In analyzing data, they were identified and classified in the appropriate headings on the cohesion analysis sheet. Then, it is classified into sentences for Grammatical and Lexical Cohesion analyzing process and interpreting each student’s writing task.